2021
DOI: 10.3390/biomedicines9121804
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Prognosis and Immunological Value of the SLC35A (Solute Carrier 35A) Family Genes in Human Breast Cancer

Abstract: According to statistics 2020, female breast cancer (BRCA) became the most commonly diagnosed malignancy worldwide. Prognosis of BRCA patients is still poor, especially in population with advanced or metastatic. Particular functions of each members of the solute carrier 35A (SLC35A) gene family in human BRCA are still unknown regardless of awareness that they play critical roles in tumorigenesis and progression. Using integrated bioinformatics analyses to identify therapeutic targets for specific cancers based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
(81 reference statements)
2
12
1
Order By: Relevance
“…A recent CRISPR-Cas9 screening in vivo 37: 262-269 (2023) identified an increased resistance to the DNA-damaging agent cisplatin in the SLC35A2-deficient cells (15). MetaCore pathway analysis of SLC35A2 co-expressed genes suggests that SLC35A2 may play a role in cell cycle regulation (4). Nonetheless, we found that cell growth was not affected by modulation of SLC35A2 expression in the present study.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A recent CRISPR-Cas9 screening in vivo 37: 262-269 (2023) identified an increased resistance to the DNA-damaging agent cisplatin in the SLC35A2-deficient cells (15). MetaCore pathway analysis of SLC35A2 co-expressed genes suggests that SLC35A2 may play a role in cell cycle regulation (4). Nonetheless, we found that cell growth was not affected by modulation of SLC35A2 expression in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…A recent bioinformatics study disclosed that SLC35A2 was substantially related to poor prognosis in patients with breast cancer (4). The human SLC35A2 gene is located on chromosome Xp11.23 and encodes the uridine diphosphate (UDP)-galactose transporter.…”
mentioning
confidence: 99%
“…Therefore, many studies in recent years have focused on analyzing the function of SLC35 family in diseases including cancer. Several literatures have pointed out that SLC35A3 plays an important role in the occurrence and development of T-cell lymphoblastoma, pancreatic cancer, and breast cancer, and can be used as an early warning marker for the above cancers [17][18][19]. The clinical signi cance of SLC35A3 in CRC…”
Section: Discussionmentioning
confidence: 99%
“…The solute carrier 35A (SLC35A) gene family to be pivotal in the occurrence and development of tumor. SLC35A3 is highly expressed in triple negative breast cancer (TNBC) cell lines HCC1395, HCC1187 and MDAMB436 [17]. Research shows that SLC35A3 is the pathogenic gene of T-cell lymphoblastoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of overexpression of SHCBP1 in breast cancer has been studied, and cellular experiments have demonstrated that this gene directly regulates breast cancer cell proliferation and promotes the cell cycle [ 44 ]. SLC35A2 is associated with hypoxia-inducible factors, heat shock proteins, transcription factors, and DNA damage-associated signaling and is involved in the regulation of neutrophil and macrophage polarization in breast cancer [ 45 ]. In summary, the majority of the genes associated with mRNAsi of breast cancer in this study are closely related to cancer development or immune regulation of breast cancer, and it is reasonable to use this constructed prognostic model for clinical prognostic guidance.…”
Section: Discussionmentioning
confidence: 99%